Prevalence of Methicillin Resistant Staphylococcus aureus Carriage Amongst Healthcare Workers of Critical Care Units in Tertiary Hospitals of Jashore, Bangladesh - Shah, SM Tanjil; Chakrovarty, Tanay; Atiqua, -; Roy, Pravas Chandra; Islam, Md Tanvir; Rahman, Sabita Rezwana; Rahman, Md Majibur (Bangladesh Journal of Microbiology, 2023)
Staphylococcus aureus is responsible for numerous mild to severe diseases in humans in both hospital and community settings. This problem is getting even worse for multi-drug resistant S. aureus. Healthcare workers (HCWs) are in a threat of MRSA carriage and can serve as reservoirs. Therefore, this can lead to subsequent infection and cause a nosocomial outbreak of MRSA. This cross-sectional study involved 85 healthcare workers (HCWs) from surgery units and critical care units of five different tertiary hospitals at Jashore, Bangladesh. Nasal swab samples were collected and inoculated on selective Mannitol Salt Agar (MSA) media. S. aureus was confirmed by selective growth on MSA and detection of the presence of the femA gene. Antibiotic susceptibility pattern was determined for all S. aureus isolates. Methicillin resistance was detected using both disc diffusion assay and gene specific polymerase chain reaction. S. aureus specific staphylococcal protein A (Spa) typing was also done by sequence analyses of PCR products. Among the 85 enrolled HCW personnel, 34 (40%) were carrying S. aureus followed by the S. intermedius (N=32). An overall prevalence of MRSA was found to be 3.53% (3/85). However, all the strains were susceptible to vancomycin. Additionally, 100% sensitivity was found against Trimethoprim/sulfamethoxazole and Linezolid. Sequence analysis of Spa PCR product revealed that all S. aureus isolates were of t304 spa type. None of the S. aureus was a biofilm former. This study was only a survey on the prevalence of MRSA among HCWs. Integrated surveillance for MDR MRSA carriage among HCWs is warranted to control bursts of nosocomial infections effectively. It is strongly recommended to maintain good microbiological and personal hygiene practices by HCWs. Bangladesh J Microbiol, Volume 39, Number 2, December 2022, pp 60-66